Pengaruh Penerapan SIA, SPI dan Peran Audit Internal Terhadap Kualitas Laporan Keuangan Pada Indojaya Group - Monika Muji Astuti; Suprantiningrum Suprantiningrum (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of the application of accounting information systems, internal control systems, roles and internal auditors on the quality of Indojaya Group's financial reports. This research is a quantitative research with data analysis using multiple linear regression. The population in this study were employees of the Indojaya group who work as accountants totaling 37 employees and the sampling in this study used the census method, where all members of the population were sampled. Collecting data using a questionnaire method given to respondents to be filled out. The results of this study indicate that the application of accounting information systems, internal control systems and the role of internal audit have a significant positive effect on the quality of financial reports